CUSTOMER SATISFACTION DEVELOPMENT STRATEGY FOR ONLINE TRANSPORTATION USERS IN THE COVID-19 ERA (STUDY ON KEK ONLINE IN TEBING TINGGI) - Margareth Sagala, Yomeini; Siregar, Aisyah (RADJA PUBLIKA, 2022)
This study aims to find out what development strategy is right for Oke Jek to create customer satisfaction during this covid-19 pandemic. Oke-jek is one of the online transportation services in the city of Tebing Tinggi which started operating in 2019. This study uses a qualitative type of research with primary data and secondary data collected from interviews, observations and documentation which includes 7 respondents and is supported by theory. development, marketing and customer satisfaction theory. The method used in this research is SWOT analysis by analyzing the internal (IFE) and external (EFE) environment. The results showed that the development strategy that was carried out by Oke Jek on the IFE and EFE matrices resulted in strengths and weaknesses with a score of 1.45, opportunities and threats with a score of 1, These 15 positions are in quadrant I, which means they indicate the Aggressive Strategy. Furthermore, from the results of the identification of the SWOT analysis, four alternative strategies are produced, namely SO Strategy, WO Strategy, ST Strategy, and WT Strategy.